Safety and feasibility of red cell exchange for sickle cell disease across Canada. Issue 1 (August 2016) - Ward, Richard; Barth, David; Couban, Stephen; Naessens, Veronique; Ritchie, Bruce; Yenson, Paul; Kuo, Kevin
Abstract: We outline a case whereby RBCX was successfully provided over disparate geographical areas and time zones in Canada and overcame the logistical challenges of coordinating care across four different health care systems with the application of modern telecommunication technologies. We present this case as a model for other SCD providers and patients.